2004
DOI: 10.1097/01.fjc.0000138164.88740.f8
|View full text |Cite
|
Sign up to set email alerts
|

Ciglitazone Inhibits Oxidized-Low Density Lipoprotein Induced Immune Maturation of Dendritic Cells

Abstract: Our study suggested that one of the anti-inflammatory mechanisms of PPAR-gamma agonist ciglitazone was mediated by inhibiting the ox-LDL induced maturation and immune function of DCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Ligand-activated PPARγ decreased the inflammatory response in atherosclerogenic cells (29,30). The previous study from our team also showed that the PPARγ agonist ciglitazone could effectively inhibit ox-LDL-induced DCs maturation (8).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Ligand-activated PPARγ decreased the inflammatory response in atherosclerogenic cells (29,30). The previous study from our team also showed that the PPARγ agonist ciglitazone could effectively inhibit ox-LDL-induced DCs maturation (8).…”
Section: Discussionmentioning
confidence: 66%
“…DCs present in normal arteries are immature and become mature during atherogenesis, and emergence of dendritic cells in rupture-prone regions of vulnerable carotid plaques was documented (7). Proatherogenic factors such as oxidized low-density lipoproteins (ox-LDL) (8,9), advanced glycation end products (10), and C-reactive protein (CRP) (11) were reported to induce DC maturation and subsequently resulting in T-lymphocyte activation. Therefore, an agent able to inhibit the function of DCs may be beneficial in the treatment of atherosclerotic disease (12).…”
Section: Introductionmentioning
confidence: 99%
“…61 During the last few years, the mechanisms and factors affecting the differentiation and maturation of DCs have been intensely studied in both in vitro and in vivo experimental settings, relevant to atherosclerosis. [128][129][130][131][132][133][134][135][136][137][138] It has been shown that Apolipoprotein A-I, the major protein component of serum high-density lipoproteins, inhibits DC differentiation and maturation. 132 PPAR-a agonists ciglitazone and fenofibrate also inhibit oxLDL-induced maturation and immune functions of DCs in vitro.…”
Section: Tissue Microenvironment In Atherosclerosis and DC Functionmentioning
confidence: 99%
“…132 PPAR-a agonists ciglitazone and fenofibrate also inhibit oxLDL-induced maturation and immune functions of DCs in vitro. 133,134 Advanced glycosylation end products can promote atherosclerosis by inducing maturation of DCs. 135 In advanced atherosclerotic plaques, especially in areas around the lipid cores which lack neovascularization, DC function can be affected by hypoxia.…”
Section: Tissue Microenvironment In Atherosclerosis and DC Functionmentioning
confidence: 99%
“…in 2004, luo et al (47) suggested that the peroxisome proliferator activated receptor (PPar)-γ agonist ciglitazone inhibited the ox-ldl-induced maturation and immune functions of dcs. More recently, Shi et al (48) observed that the PPar-α agonist fenofibrate, which has favorable effects on the development of aTS, also inhibited the ox-ldl-induced immune maturation of dcs.…”
Section: Dendritic Cells As Possible Targets In the Treatment Of Athementioning
confidence: 99%